ANALYSIS OF POEM ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Poetry is one of the richest forms of literature, which in itself includes all elements of language a human learns; by elements, the focus is on the rhetorical devices. The witty use of terms used in the reference to things is represented by the rhetorical devices. The aim of the study is to identify the types of creative references used by the poets in order to distinguish their style of writing and group the work into segments. On the basis of each such prominent feature such as rhymes or alliteration, one can determine the boundary or similarity percentage among the poems, which can then be further extended to compare the poet's writing style. The analysis technique is useful for examining different poets of the modern and renaissance periods, since it can be helpful in contrasting their way of putting things into words.